2002
DOI: 10.1001/archotol.128.9.1026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Audiological Features in Auditory Neuropathy

Abstract: Management of AN in children requires serial clinical and audiometric evaluations, with a prominent role for behavioral testing. Prematurity, genetics, and hyperbilirubinemia appear to be significant factors in the development of AN; hyperbilirubinemia can be associated with spontaneous improvement of hearing thresholds. For those children not benefiting from amplification or FM systems, cochlear implantation remains a potentially successful method of habilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
173
1
26

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(212 citation statements)
references
References 22 publications
12
173
1
26
Order By: Relevance
“…A subsequent study from the US reported a prevalence rate of 5.1% in a population of children with hearing loss. 8 Although the rate of SNHL in the NICU infant population is 10 times more common than for normal term infants, the prevalence of AN in this same population is not established. Stein 14 reported an occurrence of AN of 4 per 100 in a consecutive series of admissions to an infant special care nursery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent study from the US reported a prevalence rate of 5.1% in a population of children with hearing loss. 8 Although the rate of SNHL in the NICU infant population is 10 times more common than for normal term infants, the prevalence of AN in this same population is not established. Stein 14 reported an occurrence of AN of 4 per 100 in a consecutive series of admissions to an infant special care nursery.…”
Section: Discussionmentioning
confidence: 99%
“…8,3,15 Bilirubin is a known neuronal toxin, and it may play a role in the etiology of AN. [16][17][18][19] In a recent study, Berg et al 12 reported an association between AN and elevated peak total bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding was surprising since selective inner hair cell loss is an uncommon pathology in both the human and animal literature. The finding was also intriguing because all three cases were preterm babies and because there are many reports in the literature of an association between AN and prematurity (Rance et al 1999;Madden et al 2002;Beutner et al 2007;Xoinis et al 2007).…”
Section: Introductionmentioning
confidence: 90%
“…Retrospective clinical studies have suggested that low birth weight and prematurity are risk factors for AN (Madden et al 2002;Beutner et al 2007;Xoinis et al 2007;Teagle et al 2010). Of course, prematurity is associated with a long list of comorbid factors including hyperbilirubinemia, hypoxia, necrotizing enterocolitis, bronchopulmonary dysplasia (Beutner et al 2007;Teagle et al 2010), and other clinical conditions also noted in the NICU charts of the premature infants in this study (Tables 1 and 2).…”
Section: Full-term Casementioning
confidence: 99%